Adolescent Contraception Before and After Pregnancy-Choices and Challenges for the Future - Anderson Borovac-Pinheiro; Fernanda Garanhani Surita; Aline D'Annibale; Rodolfo de Carvalho Pacagnella; Joao Luiz Pinto e Silva (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Objective To determine methods of contraception used by adolescents before and after pregnancy. Methods A cross-sectional study was performed, and data were collected from medical records of all teens in puerperal consultation at the Hospital da Mulher - José Aristodemo Pinotti (Caism), Universidade Estadual de Campinas (CAISM), São Paulo, Brazil, between July 2011 and September 2013. The inclusion criterionwas being 10 to 19 years old, and the exclusion criterion was having a first consultation 90 days after childbirth. Statistical analyseswere performed with averages, standard deviations, percentages, correlations and Fisher's exact tests using the SAS program, version 9.4. Results A total of 196 adolescents in postpartum consultation were included (44 days after childbirth on average). The majority was older than 14 years (89%), with an average age of 16.2 years, and the most were exclusively breast-feeding (70%). Before pregnancy, the use of any contraceptive methods was mentioned by 74% adolescents; the most frequent use was combined oral contraceptive followed by condom. The main reason for abandoning the use of contraception was the occurrence of an unintended pregnancy (41%), followed by reports of side effects (22%), behavior issues (18%) and desire for pregnancy (16%). A positive correlation was found between the age of the adolescent at the moment of childbirth, the age of menarche (r = 0.3), and the first sexual intercourse (r = 0.419). Vaginal delivery occurred in 76% of the cases. After birth, depot medroxyprogesterone acetate (DMPA) was the contraception method most frequently used (71%), followed by oral contraceptives (11.8%) and intrauterine devices (IUDs, 11.2%). Conclusions The most prescribed contraceptive method before pregnancy in adolescents who had childbirth was combined oral contraceptives. Many of the study participants had an unintended pregnancy. After childbirth, the most used contraceptive method was DMPA. To improve contraception and reduce the chance of unintended pregnancies among adolescents, we should promote the use of long-acting reversible contraceptives (LARCS).